Otimização do crescimento e desempenho de mudas de alface (Lactuca sativa L.) sob iluminação artificial no cultivo hidropônico convencional e indoor - Ferro, Rafael Basilio (2023)
Hydroponics is a soilless cultivation system with controlled water and nutrient supply that, when coupled with a protected and controlled environment, significantly mitigates losses stemming from climatic variations and reduces or eliminates the usage of chemical pesticides. Conversely, indoor cultivation represents a highly controlled system where, in addition to the composition of the nutrient solution, parameters such as temperature and relative humidity are meticulously regulated. This system is amenable to the cultivation of seedlings, sprouts, and mature plants, with artificial lighting serving as both a supplementary and primary light source. These parameters enable vertical production by stacking plants to the desired height, thereby amplifying cultivation area productivity. The primary aim of this study was to optimize and assess the development of crisp lettuce seedlings (Lactuca sativa L. cv. Ariel) produced in an indoor greenhouse using light-emitting diodes (LEDs) emitting red (660 nm), blue (440 nm), and warm white (2700K) wavelengths. These seedlings were subsequently transplanted for hydroponic production in a greenhouse environment and indoor hydroponics. In addition to the evaluation of seedlings, adult plants were subjected to agronomic assessments, including total fresh mass, root mass, aboveground mass, aboveground height, leaf count, and total SPAD chlorophyll index, as well as post-harvest analyses encompassing mineral content and phenolic compounds. The results showcased the feasibility of optimizing seedling production by reducing the indoor seedling cycle by 50% in comparison to commercially nursery-grown seedlings produced. Adult plants originating from indoor seedlings in the hydroponic system exhibited up to a 36% greater productivity compared to nursery seedlings in an identical cultivation system. Furthermore, plants cultivated indoors throughout the entire cycle with a 24-hour photoperiod in the last 11 days displayed the highest mass, thereby reflecting the highest average productivity. This substantiates the enhanced productive efficiency of the lettuce cultivar under study in the context of indoor cultivation with artificial lighting. These findings have the potential to inform and advance the development of vertical farms dedicated to seedling and plant production.